Aneurysmectomy with Partial Nephrectomy on a Living Donor Renal Allograft: A Case Report. (21st February 2013) - Paloyo, Siegfredo; Sageshima, Junichiro; Chen, Linda; Burke, George W.; Ciancio, Gaetano
Abstract : Vascular anomalies among living kidney donors are seldom encountered and their presence offers a complex opportunity for every transplant surgeon. Furthermore, there has been an increasing trend with the use of marginal or kidneys with pathology to address the shortage of organs. We report a rare case of a kidney allograft with a saccular aneurysm and renal cortical cysts for which an excision with primary repair and partial nephrectomy were done, respectively. The recipient was a 45-year-old female with lupus nephritis and significant comorbidities who had excellent recovery and outcome. With good surgical techniques, these types of grafts continue to provide acceptable outcome but safety of the donor should be of utmost importance.